Operations research an introduction - Taha, Hamdy A. (Prentice Hall, 1997)
Appropriate for a variety of junior and senior undergraduate and first year graduate courses in operations research. Among these courses are Industrial Engineering, Business Administration, Statistics, Computer Science, and Mathematics. Major revision is designed to meet the needs of beginning through advanced students with an emphasis placed on the formulation and applications aspects. Provides balanced coverage of theory, applications and computations of operations research techniques. Numerical examples are main vehicle for explaining new ideas with each numeric example followed by a set of problems. TORA and SIMNET software included in text. More than 1,000 problems.